The Effectiveness of High-dose N-acetylcysteine in Severe COVID-19 Patients - Puri Safitri Hanum; Qory’ Hanifa (KELUWIH: Jurnal Kesehatan dan Kedokteran, 2021)
Abstract—The study's objective was to describe the effect of using high doses of N-acetylcysteine on severe COVID-19 patients. N-acetyl cysteine, known as a mucolytic agent, in high doses (>1200 mg/day) is also known as glutathione boosting treatment, that may reduce proinflammatory cytokine so it may beneficial reduce the risk of severity. This study was an observational descriptive, evaluated from the length of stay of all patients with severe COVID-19 (clinical signs of pneumonia plus severe respiratory distress) and by monitoring the drug use data, laboratory data, and clinical data at Bhayangkara H.S Samsoeri Mertojoso Hospital Surabaya. The data was collected retrospectively from patients' Health Medical Records who got high dose N-acetylcysteine in October 2020 – February 2021, with standard therapy: antivirus (Remdesivir), antibiotics, vitamins, symptomatic and comorbid therapy, anticoagulant, and corticosteroids (Dexamethasone) as inclusion criteria, then described descriptively. The observation result confirmed that the use of a high dose of N-acetylcysteine (NAC) [1 x 1200 – 5000 mg] po/iv had effective and beneficial results as seen from the patients' length of stay, which was 12 days for patients without comorbid and 14 days for patients with comorbid like diabetes and/or hypertension. The use of high dose NAC showed improvement in the patients' clinical condition that is evaluated from improved oxygen saturation by 37%. In addition, the laboratory results are shown an improvement in thorax X-ray by 69% and inflammatory markers like CRP and d-dimer by 100%. Further research that uses a prospective method is needed to get a better result on the use of high-dose NAC in patients with severe COVID-19.Keywords: high dose, n-acetylcysteine, severe Covid-19 patient Abstrak—Tujuan dari penelitian ini adalah untuk mendeskripsikan efek penggunaan N-acetylcysteine ​​​​dalam dosis tinggi (>1200mg/hari) pada pasien COVID-19 yang parah (dengan gejala klinis pneumonia disertai dengan distress pernafasan berat) , dinilai dari lama rawat dan dengan pemantauan data penggunaan obat, data laboratorium, dan data klinis di RS Bhayangkara H.S Samsoeri Mertojoso Surabaya. Data dikumpulkan secara retrospektif dari Rekam Medis Kesehatan pasien yang mendapat N-asetilsistein dosis tinggi pada Oktober 2020 – Februari 2021, dengan terapi standar: antivirus (Remdesivir), antibiotik, vitamin, terapi simtomatik dan komorbiditas, antikoagulan, dan kortikosteroid (Dexametason) sebagai kriteria inklusi, kemudian dideskripsikan secara deskriptif. Hasil observasi menegaskan bahwa penggunaan N-acetylcystein (NAC) dosis tinggi [1 x 1200 – 5000 mg] po/iv memiliki hasil yang efektif dan memberi benefit dilihat dari lama rawat pasien yaitu 12 hari untuk pasien tanpa penyakit penyerta dan 14 hari untuk pasien dengan penyakit penyerta seperti diabetes dan/atau hipertensi. Penggunaan NAC dosis tinggi menunjukkan perbaikan kondisi klinis pasien yang dinilai dari peningkatan saturasi oksigen sebesar 37%. Selain itu, hasil laboratorium menunjukkan peningkatan seperti pada rontgen toraks sebesar 69%, dan penanda inflamasi seperti CRP dan d-dimer sebesar 100%. Diperlukan penelitian lebih lanjut yang menggunakan metode prospektif untuk mendapatkan hasil yang lebih baik pada penggunaan NAC dosis tinggi pada pasien COVID-19 berat.Kata kunci: dosis tinggi, pasien Covid-19 parah, n-asetilsistein